KAJIAN MAKNA: MIHRAB MASJID KONTEMPORER AL-IRSYAD KOTA BARU PARAHYANGAN - RYANTY DERWENTYANA NAZHAR (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2016)
Al-Irsyad mosque at Kota Baru Parahyangan is a religious building that has the power of narrative and full of meaning. The elements of interior and exterior are designed by the architect to deliver messages to users. One element of the interior which is the orientation for the user is the Mihrab. Mihrab of this mosque has a unique concept of shape and philosophy. The concept can contain messages that can even up on the ideology that is intended for users who use the facility, and when elements of the space is interpreted (signified), then it becomes a sign (sign). Meaning analysis method that is used is combined with analysis of the typology of signs and sign structure, that will produce a more powerful meaning of the sign. Mihrab Al-Irsyad mosque is one part of a whole section of the mosque, but its role is very important for conveying message, especially message that regarding religious ideology, which is expressed in symbols. Mihrab Al-Irsyad Kota Baru Parahyangan try to use elements of the space as a mark to describe the expression